(3YQaGf GdbdhHs - (3GdbSWfWjfj, EHQGgje Hf CMeO Hf EHQGgjes
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj fhQ bdhHfG HeUGHjM GdSfI hHYO ajbhd EHQGgje Hf CMeO Hf EHQGgje (B( (3GdMOjK Yfj eG JYQahf (B) (3cPG GdOjdej Yf Ydj QVj Gdg Yfg CQOJ Cf CcJH cdeGJ dWjaI JhVM eG Naj Ydi GdeHJOj ef Pdc WGdHG HJhajbg JYGdi hJbOS hSejJgG YQaGf GdbdhH aj GdMOjKs
(3BNQgG (B:s
(3hGdCSGfjO LeY ESfGO hGdeJhf LeY eJf hGdeQGO HGdESfGO McGjI WQjb GdeJf hGdeQGO HGdeJf eG jfJgj Edjg GdSfO eKd SeYJ hQCjJ hGddg JYGdi Gdehab hGdeQTO HdWag hefg GdeMdd hGdeJQhc hGdeWYhf Edi GdUMI hGdUhGHs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdMOjK hGdeUWdMs